(untitled) - McNeill, Dan (New York, 1993)
Imagine a technology so revolutionary that it gives computers the ability to make decisions more like human beings. Professor Lofti Zadeh masterminded "fuzzy logic"--a way of programming computers to "make decisions" bases on imprecise data and complex situations. In "Fuzzy Logic," Daniel McNeill and Paul Freiberger relate the compelling tale of this remarkable new technology, the genius who brought it to life, and how it will soon affect the lives of every one of us.
Keywords: Automatic control,Fuzzy systems,Computer industry,Competition, International,Cạnh tranh, quốc tế,Ngành công nghiệp máy tính,Điều khiển tự động; Hệ thống mờ